"La justicia indígena y su vulneración en los derechos y garantías constitucionales" - Pastrano Rosero, Edgar Paúl (2013)
The development of the present Thesis of Degree was carried out based on the thesis plan and its methodological points surrendered by the State Technical University of Quevedo, Ability of Right. In the chapter I, in the introduction is carried out a synthesis on the necessity of the indigenous justice and its vulneración in the rights and constitutional guarantees, giving this way execution to the constitutional text, considering the fundamental aspects of the rights of indigenous nationalities. The justification was carried out based on the new constitutional invigoration explaining the necessity of a radical change in the rights of indigenous towns, the objectives are also formulated: general and specific, hypothesis and the used resources are detailed. In the chapter II, the antecedents of the investigation are described in the doctrine it is stood out the thoughts of different actors. The jurisprudence takes cases in which the rights of people, towns, communities and indigenous nationalities have been affected. The legislation takes as main source the Constitution of the Republic of the Ecuador, certain Treaties and International Agreements and effective internal laws in the country. In the chapter III she/he is carried out a brief detail on the application of the methodology, the methods and used techniques, the field work with the help of surveys applied to the leaders and comuneros of the Comuna Camuendo Compañía of the Cantón Otavalo, shop participativo through a forum, data that after their tabulation, you arrived to the confirmation of the hypothesis and to carry out the report of the investigation. In the Chapter IV the tabulation of the surveys was developed carried out to comuneros and the interview to a leader of the commune, she/he was also carried out a shop participativo whose end is of interpreting the outlined queries. In the Capítulo V they consist the conclusions and recommendations and the bibliography. In the Chapter I SAW, the proposal is developed in the creation of a Room specialized in Indigenous matters in The National Court of Justice of the Ecuador